Systematic Review of Studies on Rhetorical Structure Theory (RST) (Revista de Estudos da Linguagem, 2024)
This paper presents a systematic review of studies published between 2010 and 2022 couched within the theoretical-methodological framework of Rhetorical Structure Theory (RST). Using “Publish or Perish” software, we extracted from Web 760 works related to RST and, considering the number of citations, we analyzed the first 100 results that were organized and described based on their abstracts. For didactic purposes, we classified these studies into the following criteria: (i) works that couldn’t be analyzed due to accessibility issues; (ii) works focusing on theorization and the description of various linguistic phenomena; (iii) studies using corpus creation and exploration; and (iv) investigations on computational applications in Natural Language Processing (NLP). In addition, among the data collected, we conducted a brief analysis of RST works developed by Brazilian researchers. As a result, we present an overview of RST studies in the last decade, allowing for the creation of research programs that consider the projects already developed and the advances of the area in Brazil and worldwide.